Multifocal cutaneous neoplastic vascular proliferations in a rainbow boa (Epicrates cenchria) collection with boid inclusion body disease - Broering Ferreira, Anthony; Fonteque, Joandes Henrique; Withoeft, Jéssica Aline; Assis Casagrande, Renata; da Costa, Ubirajara Maciel; Imkamp, Frank; Göller, Pauline; Baggio, Francesca; Hepojoki, Jussi; Hetzel, Udo; Kipar, Anja (PLOS ONE, 2024)
Reports on neoplastic processes in snakes are sparse regardless of their location, origin or behavior. Here, we describe the occurrence of multifocal cutaneous neoplastic processes consistent with hemangioma and hemangioendothelioma, with a differential diagnosis of angiomatosis, in a colony of native Brazilian rainbow boas (Epicrates cenchria) which also included animals affected by boid inclusion body disease (BIBD). Thirteen snakes were affected; seven of these had been introduced from other Brazilian sites years earlier, the others had been bred in house but were not offspring of knowingly affected animals. The breeding regime allowed contact between all female and male animals over the years. The cutaneous lesions were first observed over eight years ago, with additional cases detected during the three following years, but no new cases in the last five years. Two affected animals were subjected to a post mortem examination and were found to suffer from peliosis hepatis as one of the additional pathological changes. BIBD was confirmed in five of the eight examined animals, by histology, immunohistology for reptarenavirus nucleoprotein, and multiplex RT-PCR targeting the reptarenavirus S segment. Reptarenavirus infection was also detected in cells in the cutaneous neoplastic processes. PCRs for Bartonella henselae and B. quintana as well as bacterial DNA in general, performed on a pool of six skin lesions, yielded negative results, ruling out ongoing bacterial infection, like bacillary angiomatosis in humans, of the lesions. The results hint towards an association of reptarenavirus infection and BIBD with neoplastic processes which is worth further investigations.